1992
DOI: 10.1111/j.1365-3113.1992.tb00553.x
|View full text |Cite
|
Sign up to set email alerts
|

The internal phylogeny of ants (Hymenoptera: Formicidae)

Abstract: Abstract. The higher phylogeny of the Formicidae was analysed using 68 characters and 19 taxa: the 14 currently recognized ant subfamilies plus 5 potentially critical infrasubfamilial taxa. The results justified the recognition of 3 additional subfamilies: Aenictogitoninae Ashmead (new status), Apomyrminae Dlussky & Fedoseeva (new status), and Leptanilloidinae Bolton (new subfamily). A second analysis on these better delimited 17 subfamilies resulted in 24 equally most parsimonious trees. All trees showed a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(11 citation statements)
references
References 51 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…Apomyrma, in its original description (Brown et al 1971), was proposed to be closely related to the Amblyoponinae (then Amblyoponini), a contention supported by Wheeler & Wheeler (1985) and Hölldobler & Wilson (1990). other authors demurred, placing the genus in its own tribe (Apomyrmini) in the Ponerinae sensu lato (dlussky & Fedoseeva 1988) and in the Leptanillinae (Bolton 1990b;, and eventually in its own subfamily, Apomyrminae (Baroni urbani et al 1992;Bolton 1994Bolton , 2003. the "Apomyrma" sequences used by Saux et al (2004) were contaminated (P.S.…”
Section: Boudinot Be Contributions To the Formicidaementioning
confidence: 99%
See 2 more Smart Citations
“…Apomyrma, in its original description (Brown et al 1971), was proposed to be closely related to the Amblyoponinae (then Amblyoponini), a contention supported by Wheeler & Wheeler (1985) and Hölldobler & Wilson (1990). other authors demurred, placing the genus in its own tribe (Apomyrmini) in the Ponerinae sensu lato (dlussky & Fedoseeva 1988) and in the Leptanillinae (Bolton 1990b;, and eventually in its own subfamily, Apomyrminae (Baroni urbani et al 1992;Bolton 1994Bolton , 2003. the "Apomyrma" sequences used by Saux et al (2004) were contaminated (P.S.…”
Section: Boudinot Be Contributions To the Formicidaementioning
confidence: 99%
“…unlike the remainder of the leg cuticle, this patch was clearly thick and opaque. Recorded as absent by Baroni-urbani et al (1992), not recorded by Billen et al (2013). Future specimens of Martialis workers should be subjected to detailed SEM and tEM study.…”
Section: Notementioning
confidence: 99%
See 1 more Smart Citation
“…First, Cerapachyinae are phylogenetically related to army ants, both taxa belonging to the same monophyletic doryline section (Bolton, 1990;Baroni Urbani et al, 1992;Grimaldi et al, 1997;Brady, 2003). Their specialised predatory behaviour, especially the grouprecruitment raiding, was considered as an early stage towards the evolution of the legionary syndrome, leading to the huge ecitonine and doryline societies (Wilson, 1958a,b;Hölldo-bler and Wilson, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Mayr 1865;Dalla Torre 1893;Emery 1895;Borgmeier 1954). In the last decades it was mostly considered as the only genus of the subfamily Aenictinae (Bolton 1990(Bolton , 1995Baroni Urbani et al 1992) until the recent molecular phylogeny of Brady et al (2014), which showed that Aenictus belongs to a monophyletic group containing all dorylomorph genera now placed in the subfamily Dorylinae.…”
Section: Introductionmentioning
confidence: 99%